2021
DOI: 10.3390/ijms22179524
|View full text |Cite|
|
Sign up to set email alerts
|

Alisporivir Treatment Alleviates Mitochondrial Dysfunction in the Skeletal Muscles of C57BL/6NCrl Mice with High-Fat Diet/Streptozotocin-Induced Diabetes Mellitus

Abstract: Diabetes mellitus is a systemic metabolic disorder associated with mitochondrial dysfunction, with mitochondrial permeability transition (MPT) pore opening being recognized as one of its pathogenic mechanisms. Alisporivir has been recently identified as a non-immunosuppressive analogue of the MPT pore blocker cyclosporin A and has broad therapeutic potential. The purpose of the present work was to study the effect of alisporivir (2.5 mg/kg/day i.p.) on the ultrastructure and functions of the skeletal muscle mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…In the previous studies, we have shown that the long-term (3 weeks) administration of the MPT pore inhibitor alisporivir (a non-immunosuppressive analogue of cyclosporine A) to the mice with induced diabetes leads to alleviation of the eff ects of diabetic mitochondrial dysfunction in the skeletal and cardiac muscles. Moreover, alisporivir increases the rate of glucose utilization from the blood of diabetic animals during the glucose tolerance test [25,26]. In the present work, we continue to study the eff ect of alisporivir on mitochondrial dysfunction induced by hyperglycemia.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…In the previous studies, we have shown that the long-term (3 weeks) administration of the MPT pore inhibitor alisporivir (a non-immunosuppressive analogue of cyclosporine A) to the mice with induced diabetes leads to alleviation of the eff ects of diabetic mitochondrial dysfunction in the skeletal and cardiac muscles. Moreover, alisporivir increases the rate of glucose utilization from the blood of diabetic animals during the glucose tolerance test [25,26]. In the present work, we continue to study the eff ect of alisporivir on mitochondrial dysfunction induced by hyperglycemia.…”
Section: Introductionmentioning
confidence: 72%
“…Alisporivir suppresses development of mitochondrial dysfunction in the mouse lung endotheliocytes under hyperglycemia. In the previous studies, we have shown that in vivo administration of alisporivir to the mice with type II diabetes normalizes functioning of heart and skeletal muscle mitochondria [25,26]. In this work, we evaluated the eff ect of alisporivir on mitochondria functioning in the primary culture of mouse lung endotheliocytes un- der conditions of hyperglycemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in vivo study, C57BL/6NCrl mice fed with high-fat diet and induction with streptozotocin to develop a DM like mice. The DM like mice demonstrated that increased the protein expression of fission gene (DRP1) and decreased the protein expression of fusion genes MNF2 and OPA1), as well as PPARGc1a (key gene regulator in mitochondrial biogenesis) [ 43 ].…”
Section: Disorder Of Mitochondrial Dynamics and Mitochondrial Functio...mentioning
confidence: 99%